2012
DOI: 10.1007/s10059-012-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Suppresses Metastatic Activity in Brain Metastasis

Abstract: Primary lung tumors, breast tumors, and melanoma metastasize mainly in the brain where therapy is limited to surgery and radiation. To investigate the molecular basis of brain metastases, we isolated brain-trophic metastatic MDA-MB-435-LvBr2 (LvBr2) cells via left ventricle (LV) injection of MDA-MB-435 cells into immunodeficiency (NOD/ SCID) mice. Whereas parent MDA-MB-435 cells displayed an elongated morphology, LvBr2 cells were round and displayed an aggregated distribution. LvBr2 cells expressed lower β-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…Both the tissue and serum levels of miR-19b were increased as TNM stage increased, indicating the important function of miR-19b in the occurrence, progression, and metastasis of NSCLC. Several studies reported that the upregulation of miR-146a inhibits cancer metastasis (Kogo et al 2011;Hwang et al 2012;Chen et al 2013a). Rong et al (2014) found that low expression of miR-146a was associated with TNM and LNM in patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Both the tissue and serum levels of miR-19b were increased as TNM stage increased, indicating the important function of miR-19b in the occurrence, progression, and metastasis of NSCLC. Several studies reported that the upregulation of miR-146a inhibits cancer metastasis (Kogo et al 2011;Hwang et al 2012;Chen et al 2013a). Rong et al (2014) found that low expression of miR-146a was associated with TNM and LNM in patients with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In another study comparing breast cancer patients with or without brain metastasis, up-regulation of microRNA-10b was identified to be strongly associated with the development of brain metastasis [56]. Several microRNAs were able to suppress brain metastasis in breast cancer cells: 1) microRNA-7 down-regulates KLF4 in the cancer stem-like cell (CSC) population of MDA-MB-231 brain-seeking cells [57]; 2) microRNA-146a targets beta-catenin and hnRNPC in the MDA-MB-435 experimental brain metastasis model [58]; 3) microRNA-1258 targets heparanase to suppress brain metastasis in the MDA-MB-231 experimental brain metastasis model [59]. In contrast, miR-141 was shown to promote brain metastasis in several breast cancer cell lines [22].…”
Section: New Biological Insights On Brain Metastasismentioning
confidence: 99%
“…This was, however, an indirect effect purported to be mediated via the heterogeneous nuclear ribonucleoprotein C1/C2 (hnRNPC) [93]. …”
Section: Matrix Metallopeptidase 1 (Mmp-1)mentioning
confidence: 99%